2021
DOI: 10.37506/ijfmt.v15i1.13590
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Death Incidence in Healthcare Facility in Indonesia: Does Antenatal Care Matter?

Abstract: Despite having carried out maternity care in healthcare facilities, neonatal deaths still occur. A study was conducted to analyze the effect of antenatal care (ANC) on neonatal death incidence in healthcare facilities in Indonesia. The study used the 2017 IDHS data. With stratification and multistage random sampling, 13.104 women aged 15-49 years with live births in the last 5 years, who performed maternity care in the healthcare facility, were sampled. Apart from ANC, other independent variables analyzed were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
1
2
0
3
Order By: Relevance
“…This study revealed that babies from mother with pregnancy complication were more likely to die than those from mother with no pregnancy complication. This is in line with the study from Sudan [ 27 ], Jimma Ethiopia [ 12 ] and Indonesia [ 28 ]. This could be explained by the fact that pregnancy complications impair the fetus’s health and can contribute to preterm delivery, which can lead to life-threatening preterm complications, potentially increasing the risk of newborn death.…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed that babies from mother with pregnancy complication were more likely to die than those from mother with no pregnancy complication. This is in line with the study from Sudan [ 27 ], Jimma Ethiopia [ 12 ] and Indonesia [ 28 ]. This could be explained by the fact that pregnancy complications impair the fetus’s health and can contribute to preterm delivery, which can lead to life-threatening preterm complications, potentially increasing the risk of newborn death.…”
Section: Discussionsupporting
confidence: 92%
“…However, in some developing countries, access to the use of ANC services is still very minimal. Indonesia is a lowermiddle-income country with the highest maternal mortality rate in the South-East Asia region [4][5][6]. Statistically, the maternal mortality rate in 2012 was at 359 cases per 100,000 live births and decreased in 2015 to 305 cases per 100,000 live births [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have indicated that increased educational attainment is a significant predictor of improved health outcomes [ [44] , [45] , [46] ]. Conversely, a lack of education stands in the way of achieving improved health outcomes [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%